2022
DOI: 10.1002/ags3.12564
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between robotic‐assisted and laparoscopic sphincter‐preserving operations for ultra‐low rectal cancer

Abstract: Aim Sphincter‐preserving operations for ultra‐low rectal cancer include low anterior and intersphincteric resection. In low anterior resection, the distal rectum is divided by a transabdominal approach, which is technically demanding. In intersphincteric resection, a perineal approach is used. We aimed to evaluate whether robotic‐assisted surgery is technically superior to laparoscopic surgery for ultra‐low rectal cancer. We compared the frequency of low anterior resection in cases of sphincter‐preserving oper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…To date, some studies that incorporated propensity score matching have reported on the short-term outcomes of RARS [24][25][26] ; however, few have focused on anal preservation. In a single-institution, retrospective study, Kojima et al 27 showed that, compared with LARS, RARS achieved a significantly greater rate of low anterior resection with sphincter preservation in patients with ultralow rectal cancer. In our series, the distal edges of many of the tumors in the RARS group were near the anal verge and the sphincter was preserved in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…To date, some studies that incorporated propensity score matching have reported on the short-term outcomes of RARS [24][25][26] ; however, few have focused on anal preservation. In a single-institution, retrospective study, Kojima et al 27 showed that, compared with LARS, RARS achieved a significantly greater rate of low anterior resection with sphincter preservation in patients with ultralow rectal cancer. In our series, the distal edges of many of the tumors in the RARS group were near the anal verge and the sphincter was preserved in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The lithotomy position is recognized as a high-risk position for surgery-related PI 6 , 7 . In recent years, laparoscopic and robot-assisted colorectal surgeries have become common 8 10 . Laparoscopic or robot-assisted surgery performed in the lithotomy position requires the utilization of positioning devices and rotation of the operating table.…”
Section: Introductionmentioning
confidence: 99%
“…Despite some controversy about the universal bene ts of R-TME, the ROLARR trial suggested that R-TME may offer potential advantages for technically challenging patients [9]. In addition, several studies have also reported that R-TME allows surgeons to feel comfortable and achieve better results when performing technically demanding operations, such as those with a narrow pelvis or low-level tumor [10][11][12]. However, considering the additional nancial burden and time overhead of robotic surgery, it is important to screen patients who could bene t from robotic surgery.…”
Section: Introductionmentioning
confidence: 99%